A‐kinase anchoring protein AKAP95 is a novel regulator of ribosomal RNA synthesis. (16th January 2016) - Marstad, Anne; Landsverk, Ole Jørgen B.; Strømme, Olaf; Otterlei, Marit; Collas, Philippe; Sundan, Anders; Brede, Gaute
Abstract : The RNA polymerase I transcription apparatus acquires and integrates the combined information from multiple cellular signalling cascades to regulate ribosome production essential for cell growth and proliferation. In the present study, we show that a subpopulation of A‐kinase anchoring protein 95 (AKAP95) targets the nucleolus during interphase and is involved in regulating rRNA production. We show that AKAP95 co‐localizes with the nucleolar upstream binding factor, an essential rRNA transcription factor. Similar to other members of the C2 H2 ‐zinc finger family, we show, using systematic selection and evolution of ligands by exponential enrichment and in vitro binding analysis, that AKAP95 has a preference for GC‐rich DNA in vitro, whereas fluorescence recovery after photobleaching analysis reveals AKAP95 to be a highly mobile protein that exhibits RNA polymerase I and II dependent nucleolar trafficking. In line with its GC‐binding features, chromatin immunoprecipitation analysis revealed AKAP95 to be associated with ribosomal chromatin in vivo . Manipulation of AKAP95‐expression in U2OS cells revealed a reciprocal relationship between the expression of AKAP95 and 47S rRNA. Taken together, our data indicate that AKAP95 is a novel nucleolus‐associated protein with a regulatory role on rRNA production. Abstract : AKAP95 colocalizes with the essential rRNA transcription factor UBF in the nucleolus and migrates to nucleolar caps during rRNA transcription inhibition. Overexpression of AKAP95 represses rRNA synthesis while rRNA production is increased during knockdown of AKAP95, suggesting a repressive function in rRNA synthesis. Similar to other C2 H2 ‐zinc fingers AKAP95 exhibit preference for GC‐rich DNA typical for the multi copy rDNA‐genes.